The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0103-97332006000500009
|View full text |Cite
|
Sign up to set email alerts
|

Wang-Landau sampling of an asymmetric ising model: a study of the critical endpoint behavior

Abstract: We use the Wang-Landau algorithm to calculate a density of states for an asymmetric Ising model on a triangular lattice with two-and three-body interactions in an external field. An accurate density of states allows us to determine the phase diagram and to study the critical behavior of this model at and near the critical endpoint. We observe a divergence of the curvature of the spectator phase boundary at the critical endpoint in accordance with theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
8

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
(45 reference statements)
2
6
0
8
Order By: Relevance
“…(2)). Our tests [45,46] showed that the critical line T c (H) for this asymmetric Ising model is in the same universality class as the two-dimensional Q = 3 Potts model [47], as expected due to symmetry considerations. We recall that the conjectured values [47] for the critical exponents of the 2D Q = 3 Potts model are α = 1/3, β = 1/9, γ = 13/9, and ν = 5/6.…”
Section: Asymmetric Ising Modelsupporting
confidence: 79%
See 1 more Smart Citation
“…(2)). Our tests [45,46] showed that the critical line T c (H) for this asymmetric Ising model is in the same universality class as the two-dimensional Q = 3 Potts model [47], as expected due to symmetry considerations. We recall that the conjectured values [47] for the critical exponents of the 2D Q = 3 Potts model are α = 1/3, β = 1/9, γ = 13/9, and ν = 5/6.…”
Section: Asymmetric Ising Modelsupporting
confidence: 79%
“…In particular, for J = 1 and J 3 = 2 (parameters used here) there is a CE that is well-separated from a critical point at the end of the first-order phase transition line. We use Wang-Landau sampling [3][4][5] described in Sec.II with E = ∑ i j S i S j + 2 ∑ i jk S i S j S k and M = ∑ i S i to determine the density of states g(E, M), and from it we obtain thermodynamical quantities such as the magnetization, specific heat, susceptibility, order parameter [45,46], etc. Multiple, independent random walks were performed to look for unexpected behavior resulting from different random number streams as well as to allow the determination of error bars.…”
Section: Asymmetric Ising Modelmentioning
confidence: 99%
“…Using data for L = 30, 33, 36, 42 and finite-size scaling relations, the critical endpoint for L = ∞ is estimated as (T , H ) CE = (2.443(10), −2.934 (10)). Our tests [8,9] showed that the critical line T c (H ) is in the same universality class as the two-dimensional Q = 3 Potts model [10], as expected due to symmetry considerations. We recall that the conjectured values [10] for the critical exponents of the 2D Q = 3 Potts model are α = 1/3, β = 1/9, γ = 13/9, and ν = 5/6.…”
Section: (A) Is a Line Of Critical Points Denoted T C (H ) And The Dasupporting
confidence: 79%
“…We use with random walks in the two-dimensional parameter space (E, M), where E = − ij S i S j − 2 ij k S i S j S k and M = i S i , to determine the density of states g(E, M), and from it we obtain thermodynamical quantities such as the magnetization, specific heat, susceptibility, order parameter [8,9], etc. We start the simulation with a random spin configuration and, because the density of states is unknown, we simply set g(E, M) = 1 for all possible (E, M).…”
mentioning
confidence: 99%
“…Para explorar a região entre as fases, é necessária a utilização de outros métodos de simulação de Monte Carlo. Existem alguns métodos, conhecidos como métodos de histograma uniforme, que permitem acessar a região não alcançada pelo algoritmo de Metropolis, tais como o método de Wang-Landau [16][17][18] e o Método Multicanônico [19,20]. O método Wang-Landau permite um passeio aleatório no parâmetro de interesse (energia, volume ou número de partículas).…”
Section: Introductionunclassified